1995
DOI: 10.1006/bbrc.1995.1044
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic Cloning of the Human Histo-Blood Group ABO Locus

Abstract: SUMMARY: A PI phage clone containing the near complete protein coding region of the human histo-blood group ABO gene locus was isolated and characterized. The insert was estimated at « 41 kp, and an « 20 kbp BamHI fragment contained the near complete coding region as evaluated by Southern blot analysis. Intron/exon boundaries were determined and the coding region was found to span at least seven exons. In situ hybridization to metaphase chromosomes confirmed the predicted localization to 9q34. © 1995 Academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 3 publications
0
68
0
2
Order By: Relevance
“…36 The ABO gene, located on the telomeric end of the long arm of human chromosome 9 (9q34), encodes for enzymes that produce the major antigens in the ABO blood group system (fig 1). 37 The fact that some studies found an association between the ABO blood groups, a biochemical marker for variants of the ABO gene, and Achilles tendon pathology justifies investigating this region of chromosome 9 for potential candidate genes for Achilles tendon injuries. 19 31 38 It should be noted that the lack of association (ie, a negative result) of the ABO blood group with Achilles tendon injuries in some studies does not imply that one can exclude the existence of a causal variant either at the ABO locus or in close proximity (adjacent gene/s).…”
Section: Achilles Tendon Injuriesmentioning
confidence: 99%
“…36 The ABO gene, located on the telomeric end of the long arm of human chromosome 9 (9q34), encodes for enzymes that produce the major antigens in the ABO blood group system (fig 1). 37 The fact that some studies found an association between the ABO blood groups, a biochemical marker for variants of the ABO gene, and Achilles tendon pathology justifies investigating this region of chromosome 9 for potential candidate genes for Achilles tendon injuries. 19 31 38 It should be noted that the lack of association (ie, a negative result) of the ABO blood group with Achilles tendon injuries in some studies does not imply that one can exclude the existence of a causal variant either at the ABO locus or in close proximity (adjacent gene/s).…”
Section: Achilles Tendon Injuriesmentioning
confidence: 99%
“…Expression of the pAcGP67-GalNAc-T2-sol construct resulted in an almost 50-fold increase in GalNAc-transferase activity using the Muc2 substrate-peptide in the culture medium of infected cells compared with uninfected controls as well as cells infected with the blood group A glycosyltransferase (Bennett et al, 1995) (Table III). Similarly, a 50-fold increase was observed using the hCG peptide.…”
Section: Expression Of Galnac-transferase (Galnac-t2)mentioning
confidence: 99%
“…6) was determined by comparing the A(1) cDNA sequence with A(1) containing rat genomic DNA (GenBank TM accession numbers AF296761, AF469947, and AF469948). All exon-intron boundaries conformed to the GT-AG consensus rule (not shown), and their number and localization were similar to the human blood group A glycosyltransferase gene (27,28).…”
Section: Genbankmentioning
confidence: 73%
“…The reactions were analyzed on an ALF Express using the ReproGel TM Long Read (Amersham Biosciences). cDNA Cloning and Construction of Expression Plasmids-The 7.5-kb rat genomic DNA sequence was compared with the seven exons of the human blood group A glycosyltransferase (27,28) and was found to contain regions similar to human exons 3-7. From this, a partial cDNA sequence of the rat transferase was proposed, containing the stop codon in exon 7.…”
Section: Infection Of Rats By the Nematode N Brasiliensis And Isolatmentioning
confidence: 99%